The Role of Russia in Maintaining Global Equilibrium: Historical Facts and Modern Realities - G. S. Poltavchenko (Управленческое консультирование)
The purpose of the article is to study the historical place and role of Russia in the modern structure of the world.21st century had begun with the well-established opinion that after the collapse of the USSR, the hegemony of the collective West came. Western ideologists began to aggressively impose their vision of the world order on the entire planet, intoxicated by the victory in the Cold War, Washington and its satellites are particularly furious at Russia’s position. The country, which is the legal successor of the Soviet Union, which lost the Cold War, allows itself to pursue an independent policy that runs counter to the interests of the “winners”.The collective West has unleashed a full-scale hybrid war against the Russian Federation. All this is being done, on the one hand, to contain Russia, weaken it and oust it from the world political arena, up to the dismemberment or complete destruction. On the other hand, as a warning to those states that do not want to join the globalist plans of the United States. Thus, today’s confrontation between the Russian Federation and the collective West should be considered not only, and not so much as a struggle for economic interests, but as a global confrontation between neoliberalism, the unnatural ideas and “values” imposed by it, and the traditional way of life, proven by thousands years of history, on which most sovereign nations are based.